Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/apps.12213
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Values for Understanding Organizational Life: Editor’s Introduction to the Lead Article

Abstract: In this introduction to the lead article on “Values at Work”, I summarize key points made in the lead article and its commentaries including those relating to the mechanisms and boundary conditions of value–behavior relationships. I highlight links with the organizational and management literature, which pays increasing attention to the role of values in organizations. I note that there are many synergies yet to be explored between, on the one hand, work on values traditionally rooted in social and cross‐cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Literature has shown that managers' stable values influence human behaviour (Bilsky & Schwartz, 1994;Rokeach, 1973) and play a significant role in decision-making (Lichtenstein, Lichtenstein, & Higgs, 2017). Recently, Stephan (2020) reiterated the need for an understanding of the mechanisms through which values influence organisational behaviour.…”
Section: Introduction Orientationmentioning
confidence: 99%
“…Literature has shown that managers' stable values influence human behaviour (Bilsky & Schwartz, 1994;Rokeach, 1973) and play a significant role in decision-making (Lichtenstein, Lichtenstein, & Higgs, 2017). Recently, Stephan (2020) reiterated the need for an understanding of the mechanisms through which values influence organisational behaviour.…”
Section: Introduction Orientationmentioning
confidence: 99%